Pengaruh Model Problem Based Learning (PBL) Terintegrasi Pembelajaran Berdiferensiasi Terhadap Kemampuan Berpikir Kreatif Peserta Didik Pada Mata Pelajaran IPAS Kelas IV di MI Sunan Giri - Diniyah, Ayu Lestari (Experiment: Journal of Science Education, 2024)
Important skills to master in the 21st century include critical thinking, creative thinking, communication, and collaboration. Creative thinking is the ability to use one's thought processes to generate new ideas and knowledge. Preliminary research indicates that students do not yet possess strong creative thinking skills, as the current teaching models do not facilitate the development of these abilities. To foster students' creative thinking, an integrated Problem Based Learning (PBL) model with differentiated instruction can be utilized. This study aims to determine the effect of the integrated Problem Based Learning (PBL) model with differentiated instruction on the creative thinking abilities of fourth-grade students in the IPAS subject at MI Sunan Giri. This research employs a quantitative experimental method with a Pre-Experimental One-Group Pretest-Posttest design. The results indicate that the integrated Problem Based Learning (PBL) model with differentiated instruction has a significant impact on students' creative thinking abilities, with the average pretest score being 53.23 and the posttest score being 75.32.